Meningkatkan Aktivitas Dan Keterampilan Kerjasama Menggunakan Model Pembelajaran Problem Based Learning (PBL), Student Team Achievement Division (STAD), Mind Mapping dan Media Konkret Pada Muatan Bahasa Indonesia Kelas III SDN Sungai Pantai 3 - Siti Fatimah; Ratna Purwanti (Journal Educational Research and Development | E-ISSN : 3063-9158, 2024)
The problem found was the low level of activity, collaboration skills and Indonesian language learning outcomes in class III at SDN Sungai Pantai 3 which was visible in the learning process. The cause of the problem is that learning is still one-way, lack of use of learning models and media and lack of group activities. One effort to improve activities, collaboration skills and learning outcomes is through the Problem Based Learning model, Student Team Achievement Division and Mind Mapping models. The aim of this research is to describe teacher activities, student activities, analyze collaboration skills and student learning outcomes. This research uses a qualitative and quantitative approach with the type of Classroom Action Research which was carried out in four meetings. The subjects in this research were class III students at SDN Sungai Pantai 3 for the 2024/2025 academic year, the number of students was 13 people. Analysis techniques are obtained through observation, and student learning outcome data is obtained through evaluation, then analyzed using Qualitative Descriptive and Cross tabulation technique descriptive in the form of tables and graphs. The results of the research show that the teacher's activities in each department werw always carried out well to obtain “high quality good student activities alse experienced a ranking to get the very active category. student collaboration skills alse increased and reached 100%. This it can be concluded that learning using the Problem Based Learning model, Student Team Achievement Division and Mind Mapping can improve teacher activity, student activity, collaboration skills and student learning outcomes.